Case Report: Concomitant Alzheimer's and Lewy-Related Pathology Extending the Spectrum of Underlying Pathologies of Corticobasal Syndrome - Kaiserová, Michaela; Menšíková, Katerina; Tučková, Lucie; Hluštík, Petr; Kaňovský, Petr (Frontiers in Neuroscience, 2021)
Corticobasal syndrome is clinically characterized by progressive asymmetric rigidity and apraxia together with symptoms suggestive of cortical involvement and basal ganglia dysfunction. The spectrum of neurodegenerative diseases that can manifest with CBS is wide. The associations of CBS with corticobasal degeneration, progressive supranuclear palsy, Alzheimer´s disease, frontotemporal lobar degenerations, Creutzfeldt-Jakob disease or diffuse Lewy body pathology have been reported. We describe the case of a 71-year-old woman with corticobasal syndrome (CBS). The histopathological examination of brain tissue revealed concomitant pathology corresponding to the limbic stage of Lewy-related pathology and the intermediate stage of Alzheimer-type pathology. To date, there have been only a few cases with a similar combination of pathology manifesting with the CBS phenotype, which have been described in the literature. The extent and distribution of pathological changes in these cases were somewhat different from our one and significance for clinical manifestation was attributed to only one of these pathologies. In our case, we assume that both types of pathology contributed to the development of the disease, considering the presumed specific spread of both types of pathological processes according to the Braak´s staging. Our case expands the spectrum of neurodegenerative pathological processes that may manifest with the typical CBS phenotype. Also, it points out the importance of identifying specific biomarkers that would enable more accurate in vivo differential diagnosis and more accurate determination of the underlying pathological processes of these diseases.